The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18388/abp.2020_5228
|View full text |Cite
|
Sign up to set email alerts
|

MiR-542-5p regulates the progression of diabetic retinopathy by targeting CARM1

Abstract: Diabetic retinopathy (DR), as the most frequent microvascular complication of diabetes mellitus (DM), causes vision loss and blindness in adults worldwide with increasing incidence. MicroRNAs (miRNAs) are involved in the regulation of DR. However, the role of miR-542-5p is still unknown. Here, we demonstrate that miR-542-5p is down-regulated in patients with DR and in high-glucose (HG)-treated retinal pigment epithelial cells. Moreover, miR-542-5p overexpression inhibits apoptosis in retinal pigment epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…In this, the high expression of CARM1 also was found in DR patients and HG-induced RPE cells. Silencing CARM1 could effectively relieve HG-induced RPE cell injury, which was consistent with the results of previous studies [ 32 , 33 ]. In addition, we confirmed that CARM1 was targeted by miR-338-3p, and it could reverse the inhibitory effect of miR-338-3p on HG-induced RPE cell injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this, the high expression of CARM1 also was found in DR patients and HG-induced RPE cells. Silencing CARM1 could effectively relieve HG-induced RPE cell injury, which was consistent with the results of previous studies [ 32 , 33 ]. In addition, we confirmed that CARM1 was targeted by miR-338-3p, and it could reverse the inhibitory effect of miR-338-3p on HG-induced RPE cell injury.…”
Section: Discussionsupporting
confidence: 92%
“…Under the condition of HG, CARM1 was discovered to be upregulated in RPE cells and promote cell apoptosis [ 32 ]. Moreover, Guo et al suggested that miR-542-5p could target CARM1 to inhibit HG-induced RPE cell apoptosis [ 33 ]. In this, the high expression of CARM1 also was found in DR patients and HG-induced RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…CARM1 accelerated retinal pigment epithelial cell apoptosis by mediating H3R17 asymmetric dimethylation, thereby promoting the progression of DR [28]. Additionally, Guo et al revealed that CARM1 up-regulation expedited cell apoptosis in HG-stimulated retinal pigment epithelial cells via binding to miR-542-5p [29]. In our research, we verified that CARM1 level was overtly elevated in DR patients and HG-disposed hRMECs.…”
Section: Discussionsupporting
confidence: 80%
“…MiR-34a was a promoter in DR progression by targeting sirtuin-1 (SIRT1), 30 and miR-542-5p was an antipathogenic factor in DR by targeting coactivator-associated arginine methyltransferase 1 (CARM1). 31 HG was found to increase the expression of miR-128-3p in this study. The functional assays exhibited that miR-128-3p expression upregulation neutralized all those effects of HG on ARPE-19 cells.…”
Section: Discussionsupporting
confidence: 65%